Preparation method of oil shale semicoke-based recyclable mulching film

Pretreatment of oil shale semicoke by acid etching and calcining, magnesium-aluminum hydrotalcite compounds are generated, and a styrene butadiene copolymer structure is introduced to prepare oil shale semicoke-based recyclable mulch film, solving the heating capacity of oil shale semicoke fuel The problems of low and environmental pollution have achieved high heat resistance and cold resistance of the mulch.

CN119191758APending Publication Date: 2024-12-27NORTHWEST NORMAL UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411290949.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of an oil shale semicoke-based recoverable mulching film, which is characterized in that oil shale semicoke is pretreated through acid etching and calcining processes, so that unstable variable-valence metal ions, organic matters and associated biomass such as carbonate and pyrite in the oil shale semicoke are effectively removed, and the specific surface area of the oil shale semicoke is increased; the subsequent reaction is facilitated; then a magnesium-aluminum hydrotalcite compound is generated on the surface of the pretreated oil shale semi-coke through a hydrothermal reaction method, so that the thermal stability and the cold resistance of the mulching film are enhanced; then a butylbenzene copolymer structure is introduced into the oil shale semicoke, and the butylbenzene copolymer can provide certain thermal isolation in the environment due to low thermal conductivity of the butylbenzene copolymer and reduce convection of heat, so that the mulching film is helped to keep a relatively stable temperature, and the influence of day and night temperature difference on plants is further relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste recycling, and in particular to a method for preparing an oil shale semi-coke-based recyclable ground film. Background Art

[0002] Oil shale, also known as kerogen, is a solid combustible mineral rich in organic matter and high in ash, with important industrial value. Its main feature is that shale oil can be extracted through low-temperature distillation process. Generally speaking, the oil content of oil shale is greater than 3.5%, and its organic matter content is usually high, mainly composed of sapropelic, humic or mixed materials. These characteristics make oil shale a potential source of energy, and its calorific value generally exceeds 4187 J / g, showing its calorific value advantage as a fuel.

[0003] Oil shale semi-coke is a solid waste produced when shale oil is extracted using low-temperature distillation technology from oil shale. After the shale oil is extracted, the remaining waste residue can be burned, but its calorific value is low and the freight is high, which has certain limitations. Therefore, it cannot be used as a fuel for a long time. Most of the semi-coke is usually directly discarded in nearby waste dumps. The accumulated semi-coke not only occupies a large amount of land and increases the risk of land pollution, but also contains harmful substances such as heavy metals, radioactive elements and some carcinogens. These harmful components will be released into the surrounding environment under the erosion and leakage of rainwater, causing serious soil pollution and damage to the ecological environment. Long-term pollution may also lead to the deterioration of soil structure, causing the land to gradually lose its agricultural production capacity, thereby affecting the agricultural production of surrounding communities and the quality of life of residents.

[0004] The main components of oil shale coke are kaolin and carbon black, which are very suitable for use as additives in polymer materials. If added to polymer materials, it can not only improve, enhance or give new functions to polymer materials, but also reduce the cost of polymer materials. On the other hand, it can expand the application field of oil shale coke and increase the added value of oil shale coke products.

[0005] Chinese patent document CN202110800087.0 discloses a modified oil shale semi-coke, a preparation method thereof, and an application in low-cost pipeline covering materials. By modifying the oil shale semi-coke, the mechanical properties, electrical strength, electrical insulation and cold resistance of the polymer composite material are significantly improved, but its heat resistance still needs to be further improved. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing an oil shale semi-coke-based recyclable ground film, wherein the prepared recyclable ground film has excellent mechanical properties, heat resistance and cold resistance.

[0007] In order to achieve the above object, the present invention adopts the following technical scheme: A method for preparing an oil shale semi-coke-based recyclable ground film comprises the following steps: S1. The oil shale coke is crushed and dispersed in an acid solution, stirred at 60-80° C. for 2-5 hours, then centrifuged, washed, dried, and calcined in an air atmosphere to obtain pretreated oil shale coke; S2, dissolving magnesium nitrate, aluminum nitrate and urea in water, mixing them evenly, then adding the pretreated oil shale semi-coke thereto, heating and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain an oil shale semi-coke composite material; S3, dispersing the oil shale semi-coke composite material in an ethanol aqueous solution, then adding a silane coupling agent KH570 thereto, stirring for 1-3 hours, and then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing the double bond modified oil shale semi-coke composite material in an organic solvent, then adding styrene and butadiene thereto, mixing evenly, adding initiator benzoyl peroxide, heating and stirring to react, and after the reaction is completed, filtering, washing, drying, crushing and sieving to obtain the composite modified oil shale semi-coke; S5. The composite modified oil shale coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder are placed in a high-speed mixer and mixed evenly, and then sent to a twin-screw extruder for extrusion granulation, and then the granules are blown into film by a blow molding machine to obtain the oil shale coke-based recyclable ground film.

[0008] Specifically, in step S1, the calcination temperature is 800-900° C., and the calcination time is 2-3 hours.

[0009] Specifically, in step S2, the mass ratio of magnesium nitrate, aluminum nitrate, urea and pretreated oil shale semi-coke is 2-4:1-3:4-6:5-8.

[0010] Specifically, in step S2, the temperature of the heating and stirring reaction is 75-90° C., and the time of the heating and stirring reaction is 12-18 hours.

[0011] Specifically, in step S3, the mass ratio of the oil shale semi-coke composite material to the silane coupling agent KH570 is 10-15:1-3.

[0012] Specifically, in step S4, the mass ratio of the double-bond modified oil shale semi-coke composite material, styrene, butadiene and benzoyl peroxide is 10-20:2-3:4-6:0.5-1.

[0013] Specifically, in step S4, the temperature of the heating and stirring reaction is 70-85° C., and the time of the heating and stirring reaction is 3-5 h.

[0014] Specifically, in step S5, the mass ratio of the composite modified oil shale semi-coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder is 30-40:40-60:10-15:1-3:1-2, and the antioxidant is selected from antioxidant 1010 or antioxidant 168.

[0015] Specifically, in step S5, the thickness of the oil shale semi-coke based recyclable ground film is 0.05-0.1 mm.

[0016] The present invention also provides an oil shale semi-coke-based recyclable ground film prepared by the above preparation method.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention pre-treats the oil shale coke by acid etching and calcination processes, thereby effectively removing unstable variable-valence metal ions, organic matter, and associated substances such as carbonates and pyrites in the oil shale coke, increasing the specific surface area of ​​the oil shale coke and facilitating subsequent reactions.

[0018] (2) The present invention generates magnesium-aluminum hydrotalcite compounds on the surface of pretreated oil shale semi-coke by a hydrothermal reaction method. The magnesium-aluminum hydrotalcite compounds have a layered structure that can remain stable at high and low temperatures, thereby enhancing the thermal stability and cold resistance of the ground film. In addition, the hydrotalcite has good hygroscopicity and can absorb moisture and release heat (hygroscopic heat) in a low-temperature environment, thereby mitigating the impact of low temperature on plants.

[0019] (3) The present invention introduces a butadiene copolymer structure into oil shale semi-coke through an addition reaction between double bonds. The butadiene part in the butadiene structure can provide good elasticity and toughness, making the material less prone to brittleness in a low-temperature environment. This toughness helps the mulch to maintain its mechanical properties under cold conditions. The benzene ring part in the butadiene structure can improve the thermal stability of the material. At the same time, the low thermal conductivity of the butadiene copolymer enables it to provide a certain degree of thermal isolation in the environment, reducing heat convection, thereby helping the mulch to maintain a relatively stable temperature and further mitigating the impact of the day and night temperature difference on plants. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0021] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0022] A method for preparing an oil shale semi-coke-based recyclable ground film comprises the following steps: S1. Preparation of pre-treated oil shale semi-coke The oil shale coke is crushed and dispersed in an acid solution, stirred and treated at 60-80°C for 2-5h, then centrifuged, washed, dried, and calcined in an air atmosphere to obtain pretreated oil shale coke.

[0023] In this step, the oil shale semi-coke is first crushed and passed through a 400-mesh sieve, and then treated in an acid solution.

[0024] Among them, the acid solution can be selected from sulfuric acid solution, nitric acid solution or hydrochloric acid solution, and the concentration of the acid solution is 0.5-2mol / L, for example, 0.5mol / L, 1.0mol / L, 1.5mol / L, 2mol / L can be selected, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0025] In this step, the calcination temperature in the air atmosphere is 800-900°C, for example, 800°C, 820°C, 840°C, 860°C, 880°C, and 900°C can be selected; the calcination time is 2-3h, for example, 2h, 2.5h, and 3h can be selected; but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In this step, the oil shale coke is pretreated by acid etching and calcination processes, which effectively removes unstable variable-valence metal ions, organic matter, and associated substances such as carbonates and pyrites in the oil shale coke, increases the specific surface area of ​​the oil shale coke, and facilitates subsequent reactions.

[0027] S2. Preparation of oil shale semi-coke composite material Magnesium nitrate, aluminum nitrate and urea are dissolved in water and mixed evenly, and then pretreated oil shale semi-coke is added thereto, heated and stirred for reaction, and after the reaction is completed, filtered, washed and dried to obtain an oil shale semi-coke composite material.

[0028] In this step, the mass ratio of magnesium nitrate, aluminum nitrate, urea and pretreated oil shale semi-coke is 2-4:1-3:4-6:5-8.

[0029] In this step, the temperature of the heating and stirring reaction is 75-90°C, for example, 75°C, 80°C, 85°C, and 90°C can be selected; the time of the heating and stirring reaction is 12-18h, for example, 12h, 13h, 14h, 15h, 16h, 17h, and 18h ​​can be selected; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] In this step, compared with directly blending the pretreated oil shale semi-coke and magnesium-aluminum hydrotalcite powder, the present invention generates magnesium-aluminum hydrotalcite compounds on the surface of the pretreated oil shale semi-coke through a hydrothermal reaction method, and the magnesium-aluminum hydrotalcite compounds are more evenly dispersed, avoiding the problem of performance degradation due to uneven distribution; the magnesium-aluminum hydrotalcite compounds have a layered structure, which can remain stable at high and low temperatures, thereby enhancing the thermal stability and cold resistance of the ground film; and the hydrotalcite has good hygroscopicity, can absorb moisture and release heat (hygroscopic heat) in a low temperature environment, and mitigate the impact of low temperature on plants.

[0031] S3. Preparation of double bond modified oil shale semi-coke composite material The oil shale semi-coke composite material is dispersed in an ethanol aqueous solution, and then a silane coupling agent KH570 is added thereto, stirred for 1-3 hours, and then filtered, washed, and dried to obtain a double-bond modified oil shale semi-coke composite material.

[0032] In this step, the mass fraction of the selected ethanol aqueous solution is 60-80%.

[0033] In this step, the mass ratio of the oil shale semi-coke composite material and the silane coupling agent KH570 is 10-15:1-3, for example, 10:1, 10:2, 10:3, 12:1, 12:3, 15:1, 15:2, 15:3 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In this step, the oil shale semi-coke composite material is treated by using a silane coupling agent KH570 to introduce carbon-carbon double bonds on its surface, which is beneficial to the subsequent reaction.

[0035] S4. Preparation of composite modified oil shale semi-coke The double-bond modified oil shale semi-coke composite material is dispersed in an organic solvent, and then styrene and butadiene are added thereto, mixed evenly, and an initiator benzoyl peroxide is added, heated and stirred for reaction, and after the reaction is completed, the composite modified oil shale semi-coke is obtained by filtering, washing, drying, crushing and screening.

[0036] In this step, the mass ratio of the double-bond modified oil shale semi-coke composite material, styrene, butadiene and benzoyl peroxide is 10-20:2-3:4-6:0.5-1.

[0037] In this step, the temperature of the heating and stirring reaction is 70-85°C, for example, 70°C, 75°C, 80°C, 85°C can be selected; the time of the heating and stirring reaction is 3-5h, for example, 3h, 3.5h, 4h, 4.5h, 5h can be selected; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] In this step, the butadiene copolymer structure is introduced into the oil shale semi-coke through the addition reaction between double bonds. The butadiene part in the butadiene structure can provide good elasticity and toughness, making the material less brittle in a low-temperature environment. This toughness helps the mulch to maintain its mechanical properties under cold conditions. The benzene ring part in the butadiene structure can improve the thermal stability of the material. At the same time, the low thermal conductivity of the butadiene copolymer enables it to provide a certain degree of thermal isolation in the environment, reduce heat convection, thereby helping the mulch to maintain a relatively stable temperature, and further mitigate the impact of the day and night temperature difference on plants.

[0039] S5. Preparation of oil shale semi-coke-based recyclable ground film The composite modified oil shale coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder are placed in a high-speed mixer and mixed evenly, then sent to a twin-screw extruder for extrusion granulation, and then the granules are blown into film by a blow molding machine to obtain the oil shale coke-based recyclable ground film.

[0040] In this step, the mass ratio of the composite modified oil shale semi-coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder is 30-40:40-60:10-15:1-3:1-2.

[0041] Wherein, the antioxidant is selected from antioxidant 1010 or antioxidant 168.

[0042] In this step, the mixing temperature in the high-speed mixer is 60-80° C., and the mixing time is 10-20 min.

[0043] The extrusion temperature of the extruder is 150-160°C; the blowing temperature of the blow molding machine is 160-180°C, and the thickness of the blown film is 0.05-0.1mm.

[0044] The present invention is further illustrated below by means of specific embodiments. Oil shale coke was purchased from Shenmu Chuangyou Energy Technology Co., Ltd.; the brand of polyethylene resin: DFDA-7042, was purchased from Dongguan Huaxinfa Plastic Raw Materials Co., Ltd.; the brand of maleic anhydride grafted polyethylene: XR-14L, was purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.; the mesh size of talcum powder was 1200 mesh.

[0045] Example 1 A method for preparing an oil shale semi-coke-based recyclable ground film comprises the following steps: S1. 100 g of oil shale coke was crushed and passed through a 400-mesh sieve, dispersed in 1 L of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, then centrifuged, washed, dried, and calcined at 800° C. for 3 h in an air atmosphere to obtain pretreated oil shale coke; S2, dissolving 20g of magnesium nitrate, 10g of aluminum nitrate and 40g of urea in 800mL of water, mixing them evenly, then adding 50g of pretreated oil shale semi-coke thereto, heating and stirring at 75°C for 18h, and after the reaction is completed, filtering, washing and drying to obtain an oil shale semi-coke composite material; S3, dispersing 50 g of the oil shale semi-coke composite material in 500 mL of 75 wt% ethanol aqueous solution, then adding 5 g of silane coupling agent KH570 thereto, stirring at 40° C. for 2 h, then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 100g of the double-bond modified oil shale semi-coke composite material in 2L of organic solvent DMF, then adding 20g of styrene and 40g of butadiene thereto, mixing evenly, adding 5g of initiator benzoyl peroxide, heating and stirring at 70°C for reaction for 5h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 30 parts of composite modified oil shale coke, 40 parts of polyethylene resin, 10 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1010 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05mm, thereby obtaining an oil shale coke-based recyclable ground film.

[0046] Example 2 A method for preparing an oil shale semi-coke-based recyclable ground film comprises the following steps: S1. 100 g of oil shale coke was crushed and passed through a 400 mesh sieve, dispersed in 1 L of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, then centrifuged, washed, dried, and calcined at 900° C. for 2 h in an air atmosphere to obtain pretreated oil shale coke; S2, dissolving 40g of magnesium nitrate, 30g of aluminum nitrate and 60g of urea in 1L of water, mixing evenly, then adding 80g of pretreated oil shale semi-coke thereto, heating and stirring at 90°C for 12h, and after the reaction is completed, filtering, washing and drying to obtain an oil shale semi-coke composite material; S3, dispersing 75g of the oil shale semi-coke composite material in 500mL of 75wt% ethanol aqueous solution, then adding 15g of silane coupling agent KH570 thereto, stirring at 40°C for 2h, then filtering, washing and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 200g of the double-bond modified oil shale semi-coke composite material in 2L of organic solvent DMF, then adding 30g of styrene and 60g of butadiene thereto, mixing evenly, adding 10g of initiator benzoyl peroxide, heating and stirring at 85°C for 3h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 40 parts of composite modified oil shale coke, 60 parts of polyethylene resin, 15 parts of maleic anhydride grafted polyethylene, 3 parts of antioxidant 1010 and 1 part of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05mm, thereby obtaining an oil shale coke-based recyclable ground film.

[0047] Example 3 A method for preparing an oil shale semi-coke-based recyclable ground film comprises the following steps: S1. 100 g of oil shale coke was crushed and passed through a 400-mesh sieve, dispersed in 1 L of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, then centrifuged, washed, dried, and calcined at 850° C. for 2.5 h in an air atmosphere to obtain pretreated oil shale coke; S2, dissolving 30g of magnesium nitrate, 20g of aluminum nitrate and 50g of urea in 1L of water, mixing evenly, then adding 60g of pretreated oil shale semi-coke thereto, heating and stirring at 80°C for 15h, and after the reaction is completed, filtering, washing and drying to obtain an oil shale semi-coke composite material; S3, dispersing 60g of the oil shale semi-coke composite material in 500mL of 75wt% ethanol aqueous solution, then adding 8g of silane coupling agent KH570 thereto, stirring at 40°C for 2h, then filtering, washing and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 150g of the double-bond modified oil shale semi-coke composite material in 2L of organic solvent DMF, then adding 20g of styrene and 50g of butadiene thereto, mixing evenly, adding 8g of initiator benzoyl peroxide, heating and stirring at 80°C for 4h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 35 parts of composite modified oil shale coke, 50 parts of polyethylene resin, 12 parts of maleic anhydride grafted polyethylene, 1 part of antioxidant 168 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then use a blow molding machine to blow the pellets into a film at a temperature of 160°C and a film thickness of 0.05 mm, thereby obtaining a recyclable mulch based on oil shale coke.

[0048] Example 4 A method for preparing an oil shale semi-coke-based recyclable ground film comprises the following steps: S1. 100 g of oil shale coke was crushed and passed through a 400-mesh sieve, dispersed in 1 L of a 1.0 mol / L sulfuric acid solution, stirred at 80° C. for 2 h, then centrifuged, washed, dried, and calcined at 850° C. for 2.5 h in an air atmosphere to obtain pretreated oil shale coke; S2, dissolving 25g of magnesium nitrate, 25g of aluminum nitrate and 60g of urea in 1L of water, mixing them evenly, then adding 60g of pretreated oil shale semi-coke thereto, heating and stirring at 85°C for 15h, and after the reaction is completed, filtering, washing and drying to obtain an oil shale semi-coke composite material; S3, dispersing 60g of the oil shale semi-coke composite material in 500mL of 75wt% ethanol aqueous solution, then adding 10g of silane coupling agent KH570 thereto, stirring at 40°C for 2h, then filtering, washing and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 160g of the double-bond modified oil shale semi-coke composite material in 2L of organic solvent DMF, then adding 25g of styrene and 45g of butadiene thereto, mixing evenly, adding 6g of initiator benzoyl peroxide, heating and stirring at 75°C for 4h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 32 parts of composite modified oil shale coke, 45 parts of polyethylene resin, 10 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 168 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then use a blow molding machine to blow the pellets into a film at a temperature of 160°C and a film thickness of 0.05 mm to obtain an oil shale coke-based recyclable ground film.

[0049] Comparative Example 1 A method for preparing an oil shale semi-coke-based recyclable ground film comprises the following steps: S1. 100 g of oil shale coke was crushed and passed through a 400-mesh sieve, dispersed in 1 L of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, then centrifuged, washed, dried, and calcined at 800° C. for 3 h in an air atmosphere to obtain pretreated oil shale coke; S2, dispersing 50 g of pretreated oil shale semi-coke in 500 mL of 75 wt% ethanol aqueous solution, then adding 5 g of silane coupling agent KH570 thereto, stirring at 40° C. for 2 h, then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S3, dispersing 100g of the double-bond modified oil shale semi-coke composite material in 2L of organic solvent DMF, then adding 20g of styrene and 40g of butadiene thereto, mixing evenly, adding 5g of initiator benzoyl peroxide, heating and stirring at 70°C for 5h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S4. Place 30 parts of composite modified oil shale coke, 40 parts of polyethylene resin, 10 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1010 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05mm, thereby obtaining a recyclable mulch based on oil shale coke.

[0050] Compared with Example 1, in Comparative Example 1, the pretreated oil shale semi-coke was not loaded with magnesium-aluminum hydrotalcite compounds.

[0051] Comparative Example 2 A method for preparing an oil shale semi-coke-based recyclable ground film comprises the following steps: S1. 100 g of oil shale coke was crushed and passed through a 400-mesh sieve, dispersed in 1 L of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, then centrifuged, washed, dried, and calcined at 800° C. for 3 h in an air atmosphere to obtain pretreated oil shale coke; S2, dissolving 20g of magnesium nitrate, 10g of aluminum nitrate and 40g of urea in 800mL of water, mixing evenly, then adding 50g of pretreated oil shale semi-coke thereto, heating and stirring at 75°C for 18h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain an oil shale semi-coke composite material; S3. Place 30 parts of oil shale semi-coke composite material, 40 parts of polyethylene resin, 10 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1010 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then use a blow molding machine to blow the pellets into a film at a blowing temperature of 160°C and a film thickness of 0.05 mm to obtain an oil shale semi-coke based recyclable ground film.

[0052] Compared with Example 1, Comparative Example 2 does not load the styrene-butadiene polymer structure on the oil shale semi-coke composite material.

[0053] The performance of the recyclable mulch films prepared in Examples 1-4 and Comparative Examples 1-2 was tested as follows: Tensile property test: The longitudinal tensile strength (MPa) and longitudinal elongation at break (%) of the samples were tested according to the test standard GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"; Thermal shrinkage test: The longitudinal thermal shrinkage (%) of the sample was tested using the test standard GB / T 13519-2016 "Polyethylene heat shrinkable film for packaging"; Cold resistance test: GB / T 5470-2008 standard is used for testing; The test results are shown in the following table:

[0054] Temperature regulation performance test: A stainless steel box is filled with loess 50 mm lower than the box height, a linear temperature measuring device is placed 150 mm below the soil surface, the soil surface is flat, and the recyclable mulch prepared in Example 1 of the present invention and Comparative Examples 1-2 are respectively spread on the stainless steel box, and a 100 mm thick commercially available polymer insulation layer is pasted on the sides and bottom of the box to prevent heat exchange at the bottom and sides of the box. The initial room temperature (26°C) was recorded, and the experimental device was placed in a temperature-controlled box adjustable from -40°C to 100°C. The temperature was slowly lowered and raised between 50°C and -25°C and 50°C for 24 hours, and kept constant at 50°C and -25°C for 6 hours respectively, and the temperature change at the position of the temperature measuring device was recorded; the temperature change of the recyclable mulch in Example 1 of the present invention was 6.8°C-32.4°C, the temperature change of the recyclable mulch in Comparative Example 1 was -3.6°C-34.7°C, and the temperature change of the recyclable mulch in Comparative Example 2 was -12.5°C-39.3°C. It can be seen that the recyclable mulch prepared by the present invention can maintain a relatively stable temperature and avoid the influence of the temperature difference between day and night on the plants.

[0055] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A method for preparing an oil shale semi-coke-based recyclable ground film, characterized in that: The steps include: S1. The oil shale coke is crushed and dispersed in an acid solution, stirred at 60-80° C. for 2-5 hours, then centrifuged, washed, dried, and calcined in an air atmosphere to obtain pretreated oil shale coke; S2, dissolving magnesium nitrate, aluminum nitrate and urea in water, mixing them evenly, then adding the pretreated oil shale semi-coke thereto, heating and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain an oil shale semi-coke composite material; S3, dispersing the oil shale semi-coke composite material in an ethanol aqueous solution, then adding a silane coupling agent KH570 thereto, stirring for 1-3 hours, and then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing the double bond modified oil shale semi-coke composite material in an organic solvent, then adding styrene and butadiene thereto, mixing evenly, adding initiator benzoyl peroxide, heating and stirring to react, and after the reaction is completed, filtering, washing, drying, crushing and sieving to obtain the composite modified oil shale semi-coke; S5. The composite modified oil shale coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder are placed in a high-speed mixer and mixed evenly, and then sent to a twin-screw extruder for extrusion granulation, and then the granules are blown into film by a blow molding machine to obtain the oil shale coke-based recyclable ground film.

2. The preparation method according to claim 1, characterized in that: In step S1, the calcination temperature is 800-900°C, and the calcination time is 2-3h.

3. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of magnesium nitrate, aluminum nitrate, urea and pretreated oil shale semi-coke is 2-4:1-3:4-6:5-8.

4. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the heating and stirring reaction is 75-90° C., and the time of the heating and stirring reaction is 12-18 hours.

5. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the oil shale semi-coke composite material to the silane coupling agent KH570 is 10-15:1-3.

6. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the double-bond modified oil shale semi-coke composite material, styrene, butadiene and benzoyl peroxide is 10-20:2-3:4-6:0.5-1.

7. The preparation method according to claim 1, characterized in that: In step S4, the temperature of the heating and stirring reaction is 70-85° C., and the time of the heating and stirring reaction is 3-5 h.

8. The preparation method according to claim 1, characterized in that: In step S5, the mass ratio of the composite modified oil shale semi-coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder is 30-40:40-60:10-15:1-3:1-2, and the antioxidant is selected from antioxidant 1010 or antioxidant 168.

9. The preparation method according to claim 1, characterized in that: In step S5, the thickness of the oil shale semi-coke based recyclable ground film is 0.05-0.1 mm.

10. The oil shale semi-coke based recyclable ground film prepared by the preparation method according to any one of claims 1 to 9.